Characteristics of olive ridley sea turtle (Lepidochelys olivacea) nesting beaches and hatcheries in Bantul, Yogyakarta, Indonesia - Agung Budiantoro; CATUR RETNANINGDYAH; LUCHMAN HAKIM; AMIN SETYO LEKSONO (Society for Indonesian Biodiversity, 2019)
Abstract. Budiantoro A, Retnaningdyah C, Hakim L, Leksono AS. 2019. Characteristics of olive ridley sea turtle (Lepidochelys olivacea) nesting beaches and hatcheries in Bantul, Yogyakarta, Indonesia. Biodiversitas 20: 3119-3125. We analyzed the ecological conditions of the beaches in Bantul, Java, Indonesia, in supporting the olive ridley sea turtle emergences and nesting. The study was performed at four beaches in Bantul, namely Pelangi, Samas, Goa Cemara, and Pandansimo. We collected data in areas where olive ridley sea turtle nests, such as beach width, slope, sand size, the percentage of magnetic mineral, daily temperature fluctuations, hatchlings rates, and vegetation. The results showed that Pelangi Beach was broader and steeper (31.26 m; slope 5.10°) than the rest (p<0.05). There was no difference in the sand size (diameter of 0.99 mm). The magnetic mineral content in sand ranged from 51.68-87.50%, while the daily temperature ranged from 24.3-31.0°C. The average percentage of hatchlings from 2012 to 2018 was 60.89%. Vegetation on the four beaches is almost the same, which was shrimp pine trees, runny grass, thistle, papyrus, and pandanus thorns. The average pH level of the nest hatchery was 7, supporting the hatchling embryology process. Ecologically, Pelangi Beach is the best turtle landing site in Bantul. Furthermore, transferring olive ridley sea turtle eggs to seminatural nests is recommended due to the quite high hatching rate.